The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.5194/acp-7-4149-2007
|View full text |Cite
|
Sign up to set email alerts
|

3-D polarised simulations of space-borne passive mm/sub-mm midlatitude cirrus observations: a case study

Abstract: Abstract. Global observations of ice clouds are needed to improve our understanding of their impact on earth's radiation balance and the water-cycle. Passive mm/sub-mm has some advantages compared to other space-borne cloud-ice remote sensing techniques. The physics of scattering makes forward radiative transfer modelling for such instruments challenging. This paper demonstrates the ability of a recently developed RT code, ARTS-MC, to accurately simulate observations of this type for a variety of viewing geome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 23 publications
6
44
0
Order By: Relevance
“…In Davis et al (2007), it was shown that true 3-D effects from the RT itself are small for this viewing geometry, but that "beam-filling" effects due to scene inhomogeneity are significant. The 3-D model setup has the advantage that those effects can be treated more easily than in a 1-D model.…”
Section: Class 1 "Radiances"mentioning
confidence: 94%
“…In Davis et al (2007), it was shown that true 3-D effects from the RT itself are small for this viewing geometry, but that "beam-filling" effects due to scene inhomogeneity are significant. The 3-D model setup has the advantage that those effects can be treated more easily than in a 1-D model.…”
Section: Class 1 "Radiances"mentioning
confidence: 94%
“…Much more critical is a priori knowledge of horizontal structures to decrease any systematic impact of "beam filling" (see e.g. Davis et al, 2007). The origin to the beam filling effect is horizontal inhomogeneity of the cloud field inside the footprint, but the final effect of beam filling depends on the degree of non-linearity between the cloud variables and changes in radiance.…”
Section: Methodsmentioning
confidence: 99%
“…Some research RTMs that have more sophisticated radiative transfer treatment produced comparable results with observations (e.g., Davis et al, 2007;Kulie et al, 2010). However, some of the major operational RTMs still have large biases in highfrequency microwave channels, which result in poor usage of cloudy/precipitating scenes observed by instruments such as MHS and SSMI.…”
Section: Appendix C: Comparison With Rtm Simulationsmentioning
confidence: 98%